Early exclusive breastfeeding cessation and postpartum depression: Assessing the mediating and moderating role of maternal stress and social support. - Md Jahirul Islam (Public Library of Science (PLoS), 2021)
Background Early termination of exclusive breastfeeding (EBF) and postpartum depression (PPD) are both recognized as global health problems. Recent literature reviews demonstrate a notable link between PPD and breastfeeding outcomes, however, the underlying mechanisms linking the two remain unclear. Objectives The aim of the study is to: 1) explore the comparative risk for PPD among new mothers who terminated EBF before the 6-month mark, compared to those who did not; and 2) test whether maternal stress and social support operate to mediate and/or moderate the relationship between EBF and PPD. Methods Between October 2015 and January 2016, a cross-sectional study was carried out among 426 new mothers of Bangladesh who were six months postpartum. Results Based on the multivariate logistic regression model, non-exclusively breastfeeding mothers were 7.58-fold more likely to experience PPD (95% CI [3.94, 14.59]) than exclusively breastfeeding mothers. Additionally, maternal stress and social support not only partially mediate the relationship between EBF and PPD but also substantially moderate this relationship. Specifically, the odds of PPD are significantly higher among mothers who had early EBF interruption in conjunction with increased stress levels and limited social support. Conclusions Current evidence suggests that concurrent screening for EBF difficulties and maternal stress are important red flags that might hint at complications even before mother's screen positive for PPD. Support and care from family members can provide assistance in overcoming this issue.